Green branding : the effect of green trust towards brand loyalty of the five-star hotel guest / Muhd Nabil Hanif Hassim and Mohd Raziff Jamaluddin - Muhd Nabil Hanif, Hassim; Mohd Raziff, Jamaluddin (2015)
Nowadays, many companies have given special attention on the green branding as their competitive strategy in order to develop better clientele. From empirical evidences, maximizing satisfaction and retaining customer‟s base were common but there is a gap in utilizing specific green dimension that is green trust in the environmental marketing studies. Green trust is perceived as better measurement in forming commitment and belief on the green brand and brand loyalty and therefore should be used in the green branding framework. The objective of this study is straightforward which is to examine the effect of green practice towards brand loyalty with the mediating effect of green trust and satisfaction. For hotel industry, it is imperative for the marketers to exploit green characteristics in human as a tool to develop new green products that enable them to feel like home during his/her stay in the hotel which in turn becomes his/her daily life‟s practice. The study that been conducted in this paper only serves as a conceptual paper and to reviewed back the past literature from previous researchers and scholars. The result of this study will explain the relationship between green practice and green trust towards guest‟s brand loyalty of the five-star hotel segment.